Feasibility of yeast-based domestic glutathione production in Ukraine - Dolia, Liubov; Starovoitova, Svitlana (My University, 2025)
Glutathione (GSH) is an intracellular tripeptide that plays a key role in maintaining redox homeostasis, detoxifying xenobiotics, and protecting against oxidative stress. Impaired GSH metabolism may contribute to the development of central nervous system disorders, infections, sarcopenia, chronic liver pathologies, metabolic, cardiovascular, and pulmonary diseases. GSH deficiency is one of the pathogenetic factors in the progression of chronic liver diseases, including hepatitis B and C. According to data from the Ministry of Health of Ukraine, the number of patients with viral hepatitis in 2021 was approximately 1.9 million, while projections for 2025 estimate around 1.5 million patients. Considering an average therapeutic requirement of 15 g of GSH per treatment course, the total demand amounts to 22,500 kg. Currently, there is no industrial production of GSH in Ukraine, resulting in complete import dependence. The S. cerevisiae HBSD-W08 strain demonstrates the best “productivity-to-cost” ratio and is the most promising candidate for industrial GSH biosynthesis. The establishment of domestic GSH production in Ukraine could cover approximately 0.8% of the national demand and reduce import dependency within the pharmaceutical sector. Глутатіон (GSH) – це внутрішньоклітинний трипептид, який відіграє ключову роль у підтримці окисно-відновного гомеостазу, детоксикації ксенобіотиків та захисті від оксидативного стресу. Порушений метаболізм GSH може сприяти розвитку розладів центральної нервової системи, інфекцій, саркопенії, хронічних патологій печінки, метаболічних, серцево-судинних та легеневих захворювань. Дефіцит GSH є одним із патогенетичних факторів прогресування хронічних захворювань печінки, включаючи гепатит B та C. Згідно з даними Міністерства охорони здоров'я України, кількість пацієнтів з вірусним гепатитом у 2021 році становила приблизно 1,9 мільйона, тоді як прогнози на 2025 рік оцінюють близько 1,5 мільйона пацієнтів. Враховуючи середню терапевтичну потребу 15 г GSH на курс лікування, загальний попит становить 22 500 кг. Наразі в Україні немає промислового виробництва GSH, що призводить до повної імпортозалежності.
Keywords: кафедра біотехнології і мікробіології; GSH; глутатіон; біосинтез глутатіону; glutathione; біосинтез глутатіону; glutathione